KEUTAMAAN AKHLAK DALAM PEMBANGUNAN KEUSAHAWANAN ISLAM: Centrality of Akhlaq in Islamic Entrepreneurship Development - Abdul Hamid, Solahuddin; Sa’ari, Che Zarrina; Datoâ€™ Dahaman@Dahlan, Mohd. Akram (Jurnal Syariah, 2017)
The entrepreneurial spirit is universal and transcends racial, cultural, and geographical limitations. However, this spirit is qualified further when fostered by Muslim entrepreneurs. When a career is associated with Islam, behavior needs to be managed in a holistic manner according to Islamic guidelines. Generally, the Islamic perspective encourages entrepreneurship. The only difference is that the fundamentals the religion should serve as the cornerstone of all entrepreneurial activity. This article will explain the element of akhlaq (moral practice) as one of the main components in the development of the entrepreneur’s personality through the appreciation of Islam as found in al-Qur’an, ahadith, and by scholars of Islam.